2010
DOI: 10.1051/0004-6361/201014283
|View full text |Cite
|
Sign up to set email alerts
|

Molecular absorption lines toward star-forming regions: a comparative study of HCO+, HNC, HCN, and CN

Abstract: Aims. The comparative study of several molecular species at the origin of the gas phase chemistry in the diffuse interstellar medium (ISM) is a key input in unraveling the coupled chemical and dynamical evolution of the ISM. Methods. The lowest rotational lines of HCO + , HCN, HNC, and CN were observed at the IRAM-30m telescope in absorption against the λ3 mm and λ1.3 mm continuum emission of massive star-forming regions in the Galactic plane. The absorption lines probe the gas over kiloparsecs along these lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
150
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(168 citation statements)
references
References 60 publications
18
150
0
Order By: Relevance
“…We checked that the excitation temperature of the observed CCH transition stays below 3 K, for most of the domain of physical conditions applicable to the line of sight clouds: the absorption features are formed in moderately dense gas: n(H 2 ) = 100-3000 cm −3 (Plume et al 2004;Vastel et al 2000;Godard et al 2010). These analyses have shown that, with such physical conditions, the collisional excitation of polar molecules is rather ineffective, and the excitation temperature remains close to the cosmic background temperature.…”
Section: Derivation Of Cch Column Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We checked that the excitation temperature of the observed CCH transition stays below 3 K, for most of the domain of physical conditions applicable to the line of sight clouds: the absorption features are formed in moderately dense gas: n(H 2 ) = 100-3000 cm −3 (Plume et al 2004;Vastel et al 2000;Godard et al 2010). These analyses have shown that, with such physical conditions, the collisional excitation of polar molecules is rather ineffective, and the excitation temperature remains close to the cosmic background temperature.…”
Section: Derivation Of Cch Column Densitiesmentioning
confidence: 99%
“…Models with elevated cosmic ray ionization fluxes are drawn in red, using larger symbols. The gray bars indicate the observed abundances of CH (Sheffer et al 2008), CCH (Gerin et al 2010) and c-C 3 H 2 (this work, using the scaling with CCH). massive stars.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…3), the overlap of the hyperfine components is not as severe as for the other sources, and we fitted the 532 GHz absorption profile with four Gaussian velocity components. We used the position and width as derived from the fit of the HF and HCO + spectra Godard et al 2010). …”
Section: Observationsmentioning
confidence: 99%
“…Godard et al 2010;Gerin et al 2011;Flagey et al 2013). The first results of the ionised and neutral carbon observations have recently been presented in Gerin et al (2012Gerin et al ( , 2014.…”
Section: Introductionmentioning
confidence: 99%